1973
DOI: 10.1073/pnas.70.3.773
|View full text |Cite
|
Sign up to set email alerts
|

Repeated DNA Sequences in the Heterochromatic Y Chromosome of Adult Drosophila melanogaster

Abstract: DNA isolated from Drosophila melanogaster adults (XX, XY, XXY, XYY) was used in DNA-DNA hybridization experiments on nitrocellulose filters. Filter-bound DNA of "high-heterochromatin" flies (those with one or more Y chromosomes) is more effective in forming hybrid duplexes than is XX DNA. The quantitative difference in hybridization efficiency is due primarily to molecules with a relatively high thermal stability (duplexes that dissociate in the temperature range 8090°). Hybridization experiments with DNA samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The distribution of repeated DNA sequences has also been roughly correlated with the major blocks of heterochromatin in somatic cells (Gall et al, 1971). Other experimental approaches such as analytical centrifugation (Blumenfeld and Forrest, 1971) and filter hybridization (Perreault et al, 1973) have led to the, realization that the heterochromatic Y chromosome must be relatively rich in repeated DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of repeated DNA sequences has also been roughly correlated with the major blocks of heterochromatin in somatic cells (Gall et al, 1971). Other experimental approaches such as analytical centrifugation (Blumenfeld and Forrest, 1971) and filter hybridization (Perreault et al, 1973) have led to the, realization that the heterochromatic Y chromosome must be relatively rich in repeated DNA.…”
Section: Introductionmentioning
confidence: 99%
“…To what extent are repeated DNA sequences of one chromosome shared by other chromosomes ? It has been shown (Perreault et al, 1973;Sederoff et al, 1975) that Y chromosome DNA is capable of hybridizing with DNA derived from XX flies or cell lines. Also, recent studies by Peacock et al (1977) have shown that each of five satellite DNAs are found on all of the chromosomes of the D. melanogaster complement.…”
Section: Introductionmentioning
confidence: 99%